Connected Vehicles: An Innovative Transport Technology. (2017) - Jadaan, Khair; Zeater, Sana; Abukhalil, Yazan
Abstract: The emergence of Intelligent Transportation Systems (ITS) has paved the way to new innovative prospects for improving the safety, operation, and environmental impact of transportation networks. Connected vehicle (CV), a ground-breaking initiative of "intelligent vehicles", emerging as the next wave of technology to further empower travellers. Among other benefits, this technology will help provide for increased capacity of existing transportation networks in addition to increased roadside safety for motorists through the development of an overall Intelligent Transportation System. However, before we can even consider how to integrate the technology of CV into our transport system, professionals must understand and realize its environment and how future cities to be created. This paper outlines the various aspects of the CV concept and how it will affect the transport system and urban environments over the next decade with the aim of providing transport directors and practitioners with an insight into this innovative technology. Two main types of short-range wireless communication are discussed namely Vehicle-to-Vehicle (V2 V), and Vehicle-to-Infrastructure (V2I) communication. An overview of the evolution of the CV and its operational aspects are presented together with its application. The impacts and potential operational benefits of the CV are discussed. The best practices of CV initiatives are reviewed, the broader public perception of CV applications are investigated, and the various challenges to the CV technology are identified.